2019
DOI: 10.1161/jaha.119.013441
|View full text |Cite
|
Sign up to set email alerts
|

Noncardiac Versus Cardiac Mortality in Heart Failure With Preserved, Midrange, and Reduced Ejection Fraction

Abstract: BackgroundA thorough analysis of noncardiac determinants of mortality in heart failure (HF) is missing. Furthermore, evidence conflicts on the outcome of patients with HF and no or mild systolic dysfunction. We aimed to investigate the prevalence of noncardiac and cardiac causes of death in a cohort of chronic HF patients, covering the whole spectrum of systolic function.Methods and ResultsWe enrolled 2791 stable HF patients, classified into HF with reduced ejection fraction (HFrEF; left ventricular ejection f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
51
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 34 publications
15
51
2
1
Order By: Relevance
“…As has been noted in other studies, patients in the highest LVEF quartile experienced a greater likelihood of non‐CV death than patients in the other quartiles and there was a trend toward greater likelihood of non‐CV death with increasing LVEF (online supplementary Figure ). However, we were unable to provide further breakdown of cause of death as this information was not collected in RELAX‐AHF‐2.…”
Section: Discussionsupporting
confidence: 83%
“…As has been noted in other studies, patients in the highest LVEF quartile experienced a greater likelihood of non‐CV death than patients in the other quartiles and there was a trend toward greater likelihood of non‐CV death with increasing LVEF (online supplementary Figure ). However, we were unable to provide further breakdown of cause of death as this information was not collected in RELAX‐AHF‐2.…”
Section: Discussionsupporting
confidence: 83%
“… 15 One of the most recent studies on mortality in stable outpatient CHF patients with reduced EF demonstrated a 66% survival rate with a mean follow-up of 39 months and an average age of 69 years. 36 We feel that the overall survival of our patient population is consistent with that of a typical HFrEF cohort with an average life-expectancy comparable to the findings of prior studies.…”
Section: Discussionsupporting
confidence: 88%
“…The mortality from sepsis in patients with HFrEF is greater than that for those with normal ventricular function and could be related to demand cardiac ischemia compromising already impaired ventricular function [ 7 ]. Sepsis causes a greater percentage of death in patients with mild to moderate HFrEF compared to severe CHF in which direct cardiac causes predominate [ 8 ]. Our results provide evidence that 26 mL/kg of fluid provides a more precise treatment goal in HFrEF.…”
Section: Discussionmentioning
confidence: 99%